2020
DOI: 10.3390/genes11121504
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Investigation into the Virulome, Pathogenicity, Stress Response Factors, Clonal Lineages, and Phylogenetic Relationship of Escherichia coli Strains Isolated from Meat Sources in Ghana

Abstract: Escherichia coli are among the most common foodborne pathogens associated with infections reported from meat sources. This study investigated the virulome, pathogenicity, stress response factors, clonal lineages, and the phylogenomic relationship of E. coli isolated from different meat sources in Ghana using whole-genome sequencing. Isolates were screened from five meat sources (beef, chevon, guinea fowl, local chicken, and mutton) and five areas (Aboabo, Central market, Nyorni, Victory cinema, and Tishegu) ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 89 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…Prediction of isolates’ pathogenicity toward human hosts yielded a high average probability score ( P score ≈ 0.937), close to 1.00. This pathogenicity score juxtaposed with the several virulence genes possessed by isolates, supporting their pathogenic potential to humans ( Adzitey et al, 2020 ).…”
Section: Discussionmentioning
confidence: 77%
“…Prediction of isolates’ pathogenicity toward human hosts yielded a high average probability score ( P score ≈ 0.937), close to 1.00. This pathogenicity score juxtaposed with the several virulence genes possessed by isolates, supporting their pathogenic potential to humans ( Adzitey et al, 2020 ).…”
Section: Discussionmentioning
confidence: 77%
“…Resistance genes, such as bla CTX-M and bla TEM (beta-lactamase), tet (A) and tet (B) (tetracycline), aph (3")-Ib and apha (6) (aminoglycoside), dfrA17 and dfrA14 (trimethoprim) and mdf(A) macrolide, have been found in E. coli isolated from Ghana [23,24]. In addition, virulence factors, such as lpfA, gad, mchF, iha, mchB, mchC eilA, iss, cftB and mcmA, have been associated with E. coli isolates from various meat samples in Ghana [45], revealing the potential and possibility of E. coli isolates from this study to be pathogenic, although this study did not seek to establish that. The developments of resistances are elicited by factors including the inappropriate use of antimicrobials and poor hygiene practices in healthcare and food chain setups [19,20], facilitating the transfer of resistant E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have indicated the occurrence of some virulence factors on plasmids of E. coli ( Rodriguez-Siek et al., 2005 ; Johnson et al., 2006 ; Mellata et al., 2010 ; Cyoia et al., 2015 ), K. pneumoniae ( Dolejska et al., 2013 ; Chen et al., 2020 ), Aeromonas species ( Brown et al., 1997 ), and P. aeruginosa ( Morales-Espinosa et al., 2012 ). E. coli strains possess virulence genes that play a significant role in the survival and pathogenesis of the strain in the host through bacterial adhesion ( ipfA ), hemolysis ( hlyF ), iron acquisition ( iroN and ireA ), and increased serum survival and resistance to phagocytosis ( iss and traT ) ( Sarowska et al., 2019 ; Adzitey et al., 2020 ). K. pneumoniae hypervirulent strains possess different genes that determine virulence and severity of infection in the host.…”
Section: Introductionmentioning
confidence: 99%